1997
DOI: 10.1046/j.1365-2567.1997.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reactive forbidden clones are confined to pathways of intermediate T‐cell receptor cell differentiation even under immunosuppressive conditions

Abstract: It is believed that self‐reactive forbidden T‐cell clones are generated by ‘failure’ of the pathway of T‐cell differentiation in the thymus, if it is disturbed. We examined how such forbidden clones are generated under immunosuppressive conditions. Mice were treated with an injection of deoxyspergualin, FK506, or cycloporin A. From day 3, the number of cells yielded by various organs decreased. Because of the resistance of intermediate (int) T‐cell receptor (TCR) cells (i.e. TCRint cells), they became more pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Primarily, extrathymic T cells have autoreactivity because of their limited negative selection 25–27 . Among these extrathymic T cells, CD8 + NK1·1 − TCR int cells have an allorecognition ability 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, extrathymic T cells have autoreactivity because of their limited negative selection 25–27 . Among these extrathymic T cells, CD8 + NK1·1 − TCR int cells have an allorecognition ability 20 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed the distinct functional properties of extrathymic T cells and thymus-derived T cells. Namely, extrathymic T cells (TCR int cells) eliminate abnormal self-cells (mainly self-antigens in the context of monomorphic major histocompatibility complex antigen) because of their autoreactivity (i.e., innate immunity), [21][22][23][24] whereas thymus-derived T cells (TCR high cells) interact with foreign antigens (mainly in the FIG. 7.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that chronic stress caused by immobilisation affects the number of lymphocytes in rats, but impacts on different subsets in different ways (Dominguez-Gerpe and Rey-Mendez 2001). The overall decrease in the number of circulating lymphocytes was accompanied by the increase in the number of mainly immature T lymphocytes, suggesting one of the potential mechanisms by which stress-associated immunosuppression can affect and exacerbate autoimmune diseases (Moroda et al 1997).…”
Section: Stress and The Immune Systemmentioning
confidence: 99%